Recurrent Posterior Strokes in Inflammatory Bowel Disease Patients - Amir Shaban; Brett Hymel; Maria Chavez-Keatts; Jordan J. Karlitz; Sheryl Martin-Schild (Gastroenterology Research and Practice)
Objective. To describe the stroke characteristics of patients with a history of inflammatory bowel disease (IBD). Background. A hypercoagulable state associated with IBD has been frequently implicated as a risk factor for ischemic stroke. Variable mechanisms and infrequent occurrence limit prospective clinical research on the association between IBD and stroke. Methods. We retrospectively reviewed consecutive patients with acute ischemic stroke presenting to our medical center from 7/2008 to 9/2013. Patients with a history of IBD were identified. Clinical variables were abstracted from our prospective stroke registry. Results. Over the period of five years we identified only three patients with a documented history of IBD. Each of these patients presented three times to our hospital with new strokes. Patients presented outside the window for intravenous tPA treatment on 8/9 admissions. Each one of our patients had posterior strokes on at least two separate occasions. Hypercoagulation panel showed elevated factor VIII with or without concomitant elevation of Von Willebrand factor (vWF) during almost every admission (8/9 admissions). Only one admission was associated with IBD flare. Conclusion. The association between IBD and posterior strokes is a novel finding. Factor VIII elevation may serve as a biomarker of a peristroke hypercoagulable state in patients with IBD.